The Influence Of The Creative Problem Solving (CPS) Model on Science Learning Outcomes in Terms Of Students' Multicultural Attitudes - Wapa, Andi; Arnyana, Ida Bagus Putu; Suastra, I Wayan (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The population in this study were all sixth grade elementary school students in Gugus II Ledokombo who implemented K13 with a total of 334 students. The sample consisted of 120 students who were divided into two experimental classes and two control classes using group random sampling technique. The instruments used were science learning outcomes tests and multicultural attitude questionnaires. Data analysis was carried out using ANOVA. The results of this research show that: Testing the first hypothesis, the null hypothesis was rejected and the alternative hypothesis was accepted (analysis results: "model" significance value (A) = 39.508) (Sig. < 0.050)). This means that there is a significant difference in science learning outcomes between students who take CPS learning, which is higher than students who take conventional science learning. Testing the second hypothesis, the null hypothesis is rejected and the alternative hypothesis is accepted (analysis results: significance value of "multicultural model*attitude" (A*B) = 4.468 (Sig. < 0.050)). This means that there is a significant interaction effect between learning models in science learning and students' multicultural attitudes on students' science learning outcomes. Testing the third hypothesis, the null hypothesis is rejected and the alternative hypothesis is accepted (Qtable (0.050) = 4.11, Qcount =8.518, Qcount>Qtable). This means that there is a significant difference between the science learning outcomes of students who have high multicultural attitudes when they are given treatment using CPS learning and conventional learning. Testing the fourth hypothesis, the nu hypothesis was rejected and the alternative hypothesis was accepted (Qtable (0.050) = 4.11, Qcount =4.237, Qcount>Qtable). This means that there is a significant difference between the science learning outcomes of students who have low multicultural attitudes when they are given treatment using CPS learning and conventional learning.Keywords: science learning outcomes, CPS, multicultural attitudes.DOI: 10.23960/jppk.v13.i1.2024.03